A high-temperature supramolecular-based switchable dielectric material with electrical bistability between high and low dielectric states1. Issue 12 (28th March 2015) - Chen, Cheng; Wang, Fang-Fang; Zhang, Yi; Ye, Qiong; Ye, Heng-Yun; Fu, Da-Wei
<x xml:space="preserve">Abstract</x> One new hybrid supramolecular-based phase transition compound TAPC containing macrocycle stator with electrical bistability between high and low dielectric states has been prepared.